Do Newspapers Add to CItizen Feelings of Community Closeness? ; Time for a New Look at Training for Rural-Based Development Projects - Debrah Jefferson; Jim King (Journal of Applied Communications, 1985)
"Do Newspapers Add to CItizen Feelings of Community Closeness?" by C.N. Olien, G.A. Donohue, and P.J. Tichenor ; Time for a New Look at Training for Rural-Based Development Projects by John L. Woods.